Kinesthetic Role In Motorist Learning - mukhlisin, mukhlisin (EDUCATIO : Journal of Education, 2016)
This article describes the role of kinesthetic in motor learning. It starts with a definition that kinesthetic is Generally regarded as "a feeling or awareness" of body position and body movement. But there are four factors are seemingly quite common in definitions of kinesthetic: positioning of body segments, precision of movement, balance, and spatial orientation. Any Appropriate reference explaining the reception and transmission of kinesthetic information during movement has not yet been determined to the satisfaction of all Reviews those working in this area. Traditionally, it has been assumed that the proprioceptor in the muscles represents the source of kinesthetic. The possibility of improving the capability of the kinesthetic organs of sense has been a subject of considerable interest in discussions among instructors of physical education. But there is, as yet, no convincing evidence that kinesthetic can be improved. It is Generally stated, though, that the more one practices in repeating A Certain movement, the more skillful one Becomes in making that movement. One can feel, however, that "feeling" and "balance", as the main elements of kinesthetic, can be improved through practice Increased frequency and or creation of a conducive condition.